Water Supply Network System Control Based on Model Predictive Control - Adel Abdulrahman; Nagib Nasher (Journal of King Saud University: Engineering Sciences)
An increasing demand for water due to population growth, industrial development and improvement of economic require management of water transfer and improved operation of water supply systems. This paper considers the application of a controller that is approved to be robust to improve the behavior of the water network supply system, to maintain stable operation of the water flow rate, and reduce the operational cost by manipulating the pump speed. The model predictive control (MPC) algorithm is one of the most common automatic control system that has got a wide spread application in process industry. The results show that the MPC technique gives improved performance over the PID control technique. Moreover, the MPC structure can be modified to handle the constraints applied on the system. Keywords: Water supply system, Model predictive control, Constraints